2018
DOI: 10.1371/journal.pone.0198639
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of a maize plasma membrane intrinsic protein ZmPIP1;1 confers drought and salt tolerance in Arabidopsis

Abstract: Drought and salt stress are major abiotic stress that inhibit plants growth and development, here we report a plasma membrane intrinsic protein ZmPIP1;1 from maize and identified its function in drought and salt tolerance in Arabidopsis. ZmPIP1;1 was localized to the plasma membrane and endoplasmic reticulum in maize protoplasts. Treatment with PEG or NaCl resulted in induced expression of ZmPIP1;1 in root and leaves. Constitutive overexpression of ZmPIP1;1 in transgenic Arabidopsis plants resulted in enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
1
12
0
3
Order By: Relevance
“…All in all, as shown in Figure 1 , it can be concluded that once the plants feel water scarcity under drought conditions, the protective and regulatory role of melatonin, in parallel with other anti-stress strategies, will start to prevent, alleviate, or stop the harmful effects of the stress [ 18 , 79 ]. At the cellular level, stress signals from the cell membrane inform the nucleus that “cell life is under threat” to cope with the drastic effects of the drought [ 77 , 80 ]. Quickly, the nucleus starts to activate the melatonin biosynthesis pathway from its precursor, tryptophan, in mitochondria and chloroplasts [ 75 , 76 , 81 ] through the upregulation of the melatonin-biosynthesis genes [ 53 , 65 ].…”
Section: Melatonin-induced Drought Stress Tolerancementioning
confidence: 99%
“…All in all, as shown in Figure 1 , it can be concluded that once the plants feel water scarcity under drought conditions, the protective and regulatory role of melatonin, in parallel with other anti-stress strategies, will start to prevent, alleviate, or stop the harmful effects of the stress [ 18 , 79 ]. At the cellular level, stress signals from the cell membrane inform the nucleus that “cell life is under threat” to cope with the drastic effects of the drought [ 77 , 80 ]. Quickly, the nucleus starts to activate the melatonin biosynthesis pathway from its precursor, tryptophan, in mitochondria and chloroplasts [ 75 , 76 , 81 ] through the upregulation of the melatonin-biosynthesis genes [ 53 , 65 ].…”
Section: Melatonin-induced Drought Stress Tolerancementioning
confidence: 99%
“…P5CS participates in proline biosynthesis via reducing glutamate to glutamate semialdehyde [ 24 ]. Studies showed that the overexpression of ZmPIP1;1 and ScPIP1 can increase the accumulation of proline in transgenic plants via inducing the expression of P5CS , which led to enhanced stress tolerance [ 36 , 38 , 39 ]. In this study, consistent with previous studies, the expression level of P5CS1 and the accumulation of proline in transgenic plants were also higher than those in wild-type plants ( Figure 4 B, Figure 6 B and Figure 7 A).…”
Section: Discussionmentioning
confidence: 99%
“…All in all, as shown in Figure 1, it can be concluded that once the plants feel by water scarcity under drought conditions, the protective and regulatory role of melatonin, in parallel with other antistress strategies, is starting to prevent, alleviate or stop the harmful effects of the stress [17,81]. At the cellular level, stress signal from the cell membrane informs the nucleus that "cell life under threat" to cope with the drastic effects of the drought [78,82]. Quickly, the nucleus starts to activate the melatonin biosynthesis pathway from its precursor, tryptophan, in mitochondria, and chloroplasts [76,77,83] through up-regulating the melatonin-biosynthesis genes [54,65].…”
Section: Omics Of Stomatal Movement Autophagy and Othersmentioning
confidence: 99%